The Dutch Reformed Church is continuously changing: Revision of the church order of 1998 - Strauss, Piet J. (HTS teologiese studies, 2019)
As the name of the title suggests, the Dutch Reformed Church is continuously changing or reforming. This change focuses on improvement as times change. In 1994, the Dutch Reformed Church was confronted with a new South African society built on a new paradigm, as expressed in Chapter 2 of the Constitution of the Republic of South Africa 1996. Against this background, the General Synod of 1998 amended the church order. The amendments, including employment relationships of ministers, church discipline and the relationship between church and state, echoed the new South Africa and were an attempt to operate anew from reformed constants or principles. As a changing church in a changing situation, the Dutch Reformed Church wished to reform on these points or change on the basis of reformed principles.